Safety, reactogenicity, and immunogenicity of homologous and heterologous prime-boost immunisation with ChAdOx1 nCoV-19 and BNT162b2: a prospective cohort study. Issue 11 (November 2021) - Hillus, David; Schwarz, Tatjana; Tober-Lau, Pinkus; Vanshylla, Kanika; Hastor, Hana; Thibeault, Charlotte; Jentzsch, Stefanie; Helbig, Elisa T; Lippert, Lena J; Tscheak, Patricia; Schmidt, Marie Luisa; Riege, Johanna; et al.
Summary: Background: Heterologous vaccine regimens have been widely discussed as a way to mitigate intermittent supply shortages and to improve immunogenicity and safety of COVID-19 vaccines. We aimed to assess the reactogenicity and immunogenicity of heterologous immunisations with ChAdOx1 nCov-19 (AstraZeneca, Cambridge, UK) and BNT162b2 (Pfizer-BioNtech, Mainz, Germany) compared with homologous BNT162b2 and ChAdOx1 nCov-19 immunisation. Methods: This is an interim analysis of a prospective observational cohort study enrolling health-care workers in Berlin (Germany) who received either homologous ChAdOx1 nCov-19 or heterologous ChAdOx1 nCov-19–BNT162b2 vaccination with a 10–12-week vaccine interval or homologous BNT162b2 vaccination with a 3-week vaccine interval. We assessed reactogenicity after the first and second vaccination by use of electronic questionnaires on days 1, 3, 5, and 7. Immunogenicity was measured by the presence of SARS-CoV-2-specific antibodies (full spike-IgG, S1-IgG, and RBD-IgG), by an RBD–ACE2 binding inhibition assay (surrogate SARS-CoV-2 virus neutralisation test), a pseudovirus neutralisation assay against two variants of concerns (alpha [B.1.1.7] and beta [B.1.351]), and anti-S1-IgG avidity. T-cell reactivity was measured by IFN-γ release assay. Findings: Between Dec 27, 2020, and June 14, 2021, 380 participants were enrolled in the study, with 174 receiving homologous BNT162b2 vaccination, 38 receiving homologous ChAdOx1 nCov-19 vaccination, and 104 receiving ChAdOx1 nCov-19–BNT162b2 vaccination. Systemic symptoms were reported by 103 (65%, 95% CI 57·1–71·8) of 159 recipients of homologous BNT162b2, 14 (39%, 24·8–55·1) of 36 recipients of homologous ChAdOx1 nCov-19, and 51 (49%, 39·6–58·5) of 104 recipients of ChAdOx1 nCov-19–BNT162b2 after the booster immunisation. Median anti-RBD IgG levels 3 weeks after boost immunisation were 5·4 signal to cutoff ratio (S/co; IQR 4·8–5·9) in recipients of homologous BNT162b2, 4·9 S/co (4·3–5·6) in recipients of homologous ChAdOx1 nCov-19, and 5·6 S/co (5·1–6·1) in recipients of ChAdOx1 nCov-19– BNT162b2. Geometric mean of 50% inhibitory dose against alpha and beta variants were highest in recipients of ChAdOx1 nCov-19–BNT162b2 (956·6, 95% CI 835·6–1095, against alpha and 417·1, 349·3–498·2, against beta) compared with those in recipients of homologous ChAdOx1 nCov-19 (212·5, 131·2–344·4, against alpha and 48·5, 28·4–82·8, against beta; both p<0·0001) or homologous BNT162b2 (369·2, 310·7–438·6, against alpha and 72·4, 60·5–86·5, against beta; both p<0·0001). SARS-CoV-2 S1 T-cell reactivity 3 weeks after boost immunisation was highest in recipients of ChAdOx1 nCov-19–BNT162b2 (median IFN-γ concentration 4762 mIU/mL, IQR 2723–8403) compared with that in recipients of homologous ChAdOx1 nCov-19 (1061 mIU/mL, 599–2274, p<0·0001) and homologous BNT162b2 (2026 mIU/mL, 1459–4621, p=0·0008) vaccination. Interpretation: The heterologous ChAdOx1 nCov-19–BNT162b2 immunisation with 10–12-week interval, recommended in Germany, is well tolerated and improves immunogenicity compared with homologous ChAdOx1 nCov-19 vaccination with 10–12-week interval and BNT162b2 vaccination with 3-week interval. Heterologous prime-boost immunisation strategies for COVID-19 might be generally applicable. Funding: Forschungsnetzwerk der Universitätsmedizin zu COVID-19, the German Ministry of Education and Research, Zalando SE.